GERAKAN MAHASISWA LAWAN PINJOL DAN JUDOL DEMI KEUANGAN SEHAT KELUARGA SELAMAT - Lydia Imelda Januari Putri; Ahmad Satrio Mahardika Priambada, Brian Hari Prasetyo, Rohmawan, One Sabili Rosyidin, Ahmad Fajar Si (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2026)
The Community Service Program (KKN) in Cerme Kidul Village, Cerme District, Gresik Regency aims to educate the community about the importance of household financial literacy, particularly in addressing the rise of online loans (pinjol) and online gambling (judol), which negatively impact family economic stability. The community’s lack of understanding of financial management is a major factor in the increasing number of cases of residents engaging in online loans (pinjol) and online gambling (judol). Through educational programs such as outreach, group discussions, and the distribution of information media, KKN students actively play a role in raising public awareness of the risks and negative impacts of online loans (pinjol) and online gambling. The results of the program indicate an increased public understanding of how to manage finances wisely, as well as a growing critical attitude toward illegal financial services and online gambling. It is hoped that this program will be the first step in building family economic resilience at the village level and fostering a culture of thrift and freedom from the trap of debt and online gambling.